NEIM-05 FEASIBILITY OF NAVIGATED TRANSCRANIAL MAGNETIC STIMULATION (NTMS) BASED DIFFUSION TENSOR IMAGING (DTI) TRACTOGRAPHY OF MOTOR PATHWAYS IN PATIENTS UNDERGOING STEREOTACTIC RADIOSURGERY: A CROSS-SECTIONAL DOSIMETRIC AND PATIENT OUTCOMES ANALYSIS. (5th August 2022) - Bronk, Julianna; Muir, Matthew; Michener, Hayley; Calbat, Courtney; Mackin, Dennis; Mitchell, Drew; Train, Benjamin; Farhat, Maguy; Elliot, Andrew; Prabhu, Sujit; Prinsloo, Sarah; Chung, Caroline
Abstract: BACKGROUND: No current dose limitations exist for the motor tracts during stereotactic radiosurgery (SRS) planning due to challenges in localizing this region of interest by conventional imaging. Navigated Transcranial Magnetic Stimulation (nTMS) is a non-invasive tool that utilizes electromyographic signal combined with magnetic resonance diffusion tensor imaging (DTI) to functionally map cortical motor tracts. Although nTMS is utilized for functional mapping prior to brain tumor resection, it has not been implemented in SRS planning. OBJECTIVES: To determine the feasibility of performing nTMS-based DTI in patients treated with SRS and examine the relationship between dose to functionally-defined motor tracts and patient outcomes measured by objective hand function testing and patient reported outcomes (PROs). METHODS: 16 patients treated with SRS to a brain metastasis located near anatomically-defined motor tracts were enrolled on an IRB-approved clinical trial. At median follow-up of 5.4m after SRS, patients underwent nTMS testing, brain MRI with DTI, functional outcomes testing (Pinch Dynamometer, 9-Hole Peg Test), and quality-of-life (QOL) PROs (EQ-5D-5L, MDASI-BT). nTMS-seeded DTI tractography was generated (Brainlab iPlan) and imported into GammaPlan for dosimetric evaluation. RESULTS: Tractography reconstitution was attempted for 8/16 patients and successful in 7/8 (87.5%). One patient who had prior resection of a lesion in the right pre-central gyrus failed to map in the right cortex and was unable to complete functional testing for the affected extremity. Median Dmax to the treated motor tracts was 4.6Gy [0.5-13.4Gy]. Median Dmean was 0.9Gy [0-1.2Gy]. Increased Dmax correlated with deficits in lateral pinch strength (R 2 =0.76) and 9-Hole Peg testing time (R 2 =0.61). Increased Dmean correlated with increased MDASI-BT interference scores (R 2 =0.93) and EQ5D5L score (R 2 =0.94) indicating worsened QOL. CONCLUSIONS: nTMS testing was feasible and dose to nTMS-defined motor tracts correlated with subjective and objective patient outcomes. Future steps will include characterization of motor tract dose tolerance for SRS.